Automation: punching machine / Jamal Nahar Musa, Wan Mohd Firdaus Wan Hassan and Mohamad Izam Sahab - Musa, Jamal Nahar; Wan Hassan, Wan Mohd Firdaus; Sahab, Mohamad Izam (2000)
Automation can be defined as an operation of an equipment without ANY usage (about almost 100%) human work, and instead of it, it is operated by using another system that take a major part in the working process; for example: - 1. Mechanical System. 2. Electrical System. 3. Pneumatics...etc...etc. or any system that can be considered suitable to the working process. Automation process provides the widest usage in the industrial sector. It can be categorised in several categories according to its' usage and also advantages in the process of producing a quality product. Polymer producing sector (either small, small medium, medium, etc.... etc) have grew up rapidly in our nation because of the demand concerning to the product. And our overview on one of the SMI (Small Medium Industry) factory in Malacca that produced polymer material, we've discovered that a problems occurred in the production line, and (Alhamdulillah) it given us an idea to do an upgrading project; "automation of a machine". Because we strongly believed that (Insya-Allah) we can solve the problems. Syarikat Dasar Asli Sdn. Bhd. is the factory that involved with our project analysis. As we've just mentioned before, there is a problem occurs on the production line due to the machine used in this line. We found that this machine can only be operated by man. As a result, productivity is affected meaning that it is not at an optimal level. (Alhamdulillah), after a constructive discussion with the management, permission is given to us to an upgrading work to the manual operated machine (refer to enclosed letter).